Teaching outdoor activities of uncertain dynamic environments in Physical Education: In search of an intelligent performance for the “players of wild nature” (Agora for Physical Education and Sport, 2021)
Teaching Games for Understanding (TGfU) has been shown as a methodological approach that allows teaching to be considered “beyond games”. This article justifies and explores the adaptation of some conceptual and practical tools of the TGfU model to the initiation in outdoor activities of uncertain dynamics environment (AFIA). The aim is to suggest a new way of approaching the teaching of AFIA in Physical Education that facilitates its inclusion in a students’ active lifestyle thanks to the impact on their motivation, knowledge, understanding and confidence in their own abilities.
Keywords: physical education; outdoor activities of uncertain dynamics environments; Teaching Games for Understanding; intelligent performance; teaching methodology